Gravimetric quantitative determination of packaging residues in feed from former food. Issue 8 (3rd August 2017) - Amato, Giuseppina; Desiato, Rosanna; Giovannini, Tiziana; Pinotti, Luciano; Tretola, Marco; Gili, Marilena; Marchis, Daniela
ABSTRACT: Valorisation of former foodstuff products (FFP) in feed is part of a long-term strategy for sustainability. An approach to valorise FFP outside the waste value chain is their use as an alternative source of feed materials, with a subsequent optimisation of the environmental impact of products. In the current practice of food production, food packaging is provided to ensure the maintenance of food quality and safety during transport and storage. One of the problems of reusing FFP is how to deal with packaging materials or remains that can become residues in the feed. The aim of this study is to propose a fast and sensitive gravimetric method, fit for routine official controls, for the determination of packaging residues in feed. The developed method can briefly be summarised as: (1) visual selection of the undesired ingredients which can be identified as remnants of packaging materials; (2) weighing of the selected materials; (3) defatting; (4) dehydration; (5) final weighing; and (6) reporting of weight and percentage. Moreover, the method has been validated through the determination of some of the parameters listed in Council Regulation 2004/882/EC (i.e., specificity, limit of quantification (LOQ), recovery, repeatability, within-laboratory reproducibility and measurement uncertainty).